Detection of Borrelia burgdorferi DNA in urine of patients with ocular Lyme borreliosis. Issue 5 (1st May 2001) - Pleyer, Uwe; Priem, Susanne; Bergmann, Lars; Burmester, Gerd; Hartmann, Christian; Krause, Andreas
Abstract : AIM: To evaluate the diagnostic value of the polymerase chain reaction (PCR) to detect Borrelia burgdorferi DNA in patients with ocular Lyme borreliosis. METHODS: Of 256 consecutive uveitis patients six selected individuals with clinical evidence for Lyme borreliosis and 30 patients with non-Lyme uveitis were enrolled. Lyme serology was performed by ELISA and western blotting. Urine samples were examined by an optimised nested polymerase chain reaction (PCR) protocol. RESULTS: Only four of six uveitis patients suspected for Lyme borreliosis were ELISA positive, while all six subjects showed a positive western blot. B burgdorferi PCR was positive in all of these six patients. Whereas two of the 30 controls had a positive Lyme serology, B burgdorferi DNA was not detectable by PCR in any sample from these patients. CONCLUSIONS: PCR for the detection of B burgdorferi DNA in urine of uveitis patients is a valuable tool to support the diagnosis of ocular Lyme borreliosis. Moreover, these patients often show a weak humoral immune response which may more sensitively be detected by immunoblotting.